2016
DOI: 10.1016/j.psychres.2016.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning, quality of life and clinical correlates of comorbid alcohol and drug dependence syndromes in people with schizophrenia across Europe

Abstract: Little is known about the correlates of comorbid drug and alcohol dependence in people with schizophrenia outside the USA. We tested hypotheses that dependence on alcohol or drugs would be associated with more severe symptoms, and poorer psychosocial functioning and quality of life.The EuroSC Cohort study (N=1,204), based in France, Germany and the UK, used semi-structured clinical interviews for diagnoses, and standardized tools to assess correlates. We used mixed models to compare outcomes between past-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 46 publications
(54 reference statements)
2
24
1
Order By: Relevance
“…Behaviours associated with substance misuse may require certain cognitive abilities; thus, a better cognition among patients with dual disorders would be a primary characteristic, and not secondary to the consumption of particular substances (Joyal, Hallé, Lapierre, & Hodgins, ). Consistently, in our sample, a lower impairment on negative symptoms, a common feature for subjects with comorbid schizophrenia and SUDs (Carrà et al, ), was associated with better FER performances. Also for this domain, the cognitive paradox of dually diagnosed subjects might be true.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Behaviours associated with substance misuse may require certain cognitive abilities; thus, a better cognition among patients with dual disorders would be a primary characteristic, and not secondary to the consumption of particular substances (Joyal, Hallé, Lapierre, & Hodgins, ). Consistently, in our sample, a lower impairment on negative symptoms, a common feature for subjects with comorbid schizophrenia and SUDs (Carrà et al, ), was associated with better FER performances. Also for this domain, the cognitive paradox of dually diagnosed subjects might be true.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, our recent meta‐analysis confirmed the existence of severe deficits in FER also in subjects with alcohol and substance use disorders (AUDs/SUDs) relative to healthy participants (Castellano et al, ). However, AUDs and SUDs are highly comorbid in people with schizophrenia (e.g., Carrà et al, , ). Thus, individuals with schizophrenia who misuse psychoactive substances should arguably display an additional impairment in FER.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that individuals living on their own could not properly use drugs, and it was revealed that there were many cases with multiple drug and alcohol/drug combination use. 45 Our results indicate that as a pharmaceutical factor, the use of psychotropic drugs to treat mental illness has a substantial effect on death. 46 , 47 …”
Section: Discussionmentioning
confidence: 69%
“…Increasing heterogeneity increases the value of I 2 , which allows for the selection of a fixed-effect model or a random-effect model based on the I 2 50% rate [21]; a fixed effect model will be selected if it presents heterogeneity results below 50%, and if heterogeneity is higher than 50%, a random effect model will be selected, and subgroup analysis will be performed. Factors expected to contribute to heterogeneity include the clinical characteristics of the patients, including the severity of the disease, the comorbidity, the exact diagnosis, and the duration of the disease, which have all been reported to have an effect on treatment in previous studies [22][23][24][25]. Therefore, the subgroups will be set up in consideration of clinical characteristics and types of interventions, so that the likelihood of statistical errors are reduced.…”
Section: Discussionmentioning
confidence: 99%